PENGARUH LEVERAGE, CAPITAL INTENSITY, CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP AGRESIVITAS PAJAK DIMODERASI OLEH UKURAN PERUSAHAAN - Ilman, Muhammad Fathir; Arsjah, Regina Jansen = (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2025)
This study aims to analyze the effect of leverage, capital intensity, and CSR on tax aggressiveness with firm size as a moderating variable in healthcare sector companies listed on the Indonesia Stock Exchange for the period 2018–2023, as high tax burdens encourage companies to engage in tax aggressiveness through various strategies. From 33 healthcare sector companies listed, 31 companies were selected as the sample for this study. The data used is secondary data in the form of financial reports and sustainability reports from 2018 to 2023, which were processed using moderated regression analysis while considering the requirements of classical assumption tests, including normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Hypotheses were tested using t-statistic and F-statistic tests. The research results show that leverage does not affect tax aggressiveness, capital intensity has a positive effect on tax aggressiveness, and CSR has a negative effect on tax aggressiveness. Furthermore, with the inclusion of the moderating variable, firm size, the findings conclude that firm size weakens the positive effect of leverage on tax aggressiveness, firm size weakens the positive effect of capital intensity, and firm size also weakens the positive effect of CSR on tax aggressiveness.